The Role of Plant Resources in Nigeria's Economic Recovery Agenda - Isichei, A. O. (2014)
Basically, it is the performance of plants and chemical composition that we exploit for economic and cultural purposes. Our human world has been so closely tied to plants that it is difficult to imagine human existence without them. In all life on earth, plants are the only producers and all consumers are dependent upon plants for food, fibre, wood, energy and oxygen. Knowledge of plants, their habitats. structure, metabolism and inheritance is thus the basic foundation for human survival. Plants form the bedrock of life, being the first generator of oxygen in a reducing atmosphere that characterized the early earth. Plants are thus the roots of life and human material culture depends on them. The way a people incorporate plants into their cultural traditions, religions and even cosmologies reveals much about the people themselves. People rely on plants for much more than food and shelter and people use plants in so many ways that there are a few areas of human endeavour in which they do not play an important role. Plants have determined the course of human civilization - America was discovered during the course of the search of spices. Few societies can ignore the pivotal role of agriculture and forestry, both based essentially on plants. Several environmental crises such as global warming and biodiversity loss at their core, involve plants. It could indeed be that we are so closely linked that humans often take plants for granted, something to be left to the background and not worthy of serious economic consideration. But we met plants on our planet and they have defined our 'life zones'. The late appearance of humans on the evolutionary scene laid open to us a large variety of natural resources to exploit for food and plants were the natural choice, being the only organisms that had the capability to convert solar energy to chemical energy. From them we have learnt about life and it now looks as if we still have to depend on them to sort out our environmental crisis.